Validity and reliability of the Turkish Patient-Rated Wrist Evaluation questionnaire - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2015)
Objective: The Patient-Rated Wrist Evaluation (PRWE) scale is a self-administered outcome questionnaire used to determine level of pain and disability in wrist problems. The scale includes pain (PRWE-P) and function (PRWE-F) subscales, the latter consisting of specific function (PRWE-SF) and usual (PRWE-UF) function. This study aimed to evaluate the validity and reliability of the Turkish version of the PRWE scale. Methods: Permission was sought and received from the original author of the PRWE for a Turkish translation for use in the study. The study included 110 patients (85 female and 25 male; mean age: 50.8 +/- 1.53 years; range: 18 to 85) with distal radius fracture, carpal tunnel syndrome, wrist ganglion cyst, De Quervain syndrome, Kienbock disease, and connective lesions affecting the wrist, all of whom completed the Turkish version of both the PRWE (PRWE-T) and the Disabilities of the Arm Shoulder and Hand scale (DASH). Reliability and validity of the PRWE-T scale were evaluated via an internal consistency analysis and a factor analysis respectively. The level of correlation between PRWE-T and DASH scores was also examined. Results: Cronbach's alpha coefficient was calculated as 0.86, 0.82 and 0.88 for PRWE-P, PRWE-F and PRWE-T respectively for the scale and all subscales. The PRWE-T scale was found to be highly reliable. A statistically significant correlation was found between PRWE-T and DASH in the criterion-related validity analysis (Spearman's rho=0.9). Conclusion: The PRWE-T was found to be valid and reliable. It is therefore suggested for use in evaluating patient-based pain and disability levels in routine clinical practice.
Keywords: Disability; outcome questionnaire; PRWE; Turkish version; validity; CROSS-CULTURAL ADAPTATION; EVALUATION PRWE; SWEDISH VERSION; DISABILITY; VALIDATION; GERMAN; HAND; PAIN